Thirlwall´s law and foreing capital in Brazil - CANUTO, OCTAVIANO; LUIZ FERREIRA, ALEX (Revista Momento Económico, 2009)
THIS PAPER ADDRESSES THE HYPOTHESIS OF BALANCE OF PAYMENTS CONSTRAINT TO INCOME GROWTH IN BRAZIL THROUGH AN EXTENDED VERSION OF ”THIRLWALL´S LAW” [THIRLWALL (1979)] THE PERIOD COVERED BY THE TESTS IS FROM 1949 TO 1999. WE AIM TO COMPLEMENT EXISTING APPLICATIONS OF OPEN-ECONOMY KEYNESIAN MODELS TO BRAZIL BY EXPLICITLY INTRODUCING THE EFFECTS OF NET PAYMENTS OF INTEREST, DIVIDENS AND PROFITS (OF THE BALANCE OF PAYMENT´S CURRENT ACCOUNT) ON THE DOMESTIC INCOME GROWTH RATE. ADDITIONALLY, THE PAPER PRESENTS A TEST OF GRANGER CAUSALITY REGARDING, ON THE ONE HAND, INCOME-ELASTICITIES OF EXPORTS AND IMPORTS AND ON THE OTHER, ECONOMIC GROWTH. OUR FINDINGS DO NOT REJECT THE HYPOTHESIS UNDERLYING THIRLWALL´S GROWTH LAW.